The moral costs of nastiness - Klaus Abbink; Benedikt Herrmann (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2009)
We introduce two variants of the one-shot joy-of-destruction minigame (mini-JOD). Two players are endowed with the same amount of money. They simultaneously decide whether or not to reduce the payoff of the other player at an own cost. In one treatment there was a probability that Nature would destroy the opponent's money anyway. We test whether this feature reduces the moral costs of being nasty, and find that destruction rates rise significantly, despite the absence of strategic reasons
Keywords: 330; Verhaltensökonomik; Persönlichkeitspsychologie; Spieltheorie